A preliminary account of the fruit fly fauna of Timor-Leste (Diptera: Tephritidae: Dacinae) - Bellis, Glenn A; Brito, Americo A; Jesus, Hipolito De; Quintao, Valente; Sarmento, Joaquim C; Bere, Apolinario; Rodrigues, João; Hancock, David L (Zootaxa, 2017)
Opportunistic monitoring using baited fruit fly traps throughout Timor-Leste revealed the presence of 16 species of Bactrocera and one species of Dacus, all of which are previously reported from the region. Sampling of a range of commercial fruit species detected an additional species, B. latifrons, and revealed that nine species are attacking commercial fruits and vegetables. A key for separating these species is provided. New host records were found for B. minuscula, B. floresiae and B. bellisi. Variation in the morphology of B. minuscula, B. floresiae and an undescribed species and within B. albistrigata confounded attempts at accurate identification of some specimens.